Four new records and two new species of Phytoseiidae (Acari: Mesostigmata) from Turkey, with a key to the Turkish species - Döker İsmai̇l; Stathakis, Theodoros I.; Kazak Cengi̇z; Karut Kami̇l; Papadoulis, Georgios Th. (Zootaxa, 2014)
Four species of phytoseiid mites namely Neoseiulus knappi Zannou, Moraes, Ueckermann & Oliveira, Typhlodromus (Typhlodromus) octogenipilus Kreiter, Tixier & Duso, Typhlodromus (T.) phialatus Athias-Henriot, and Typhloseiella isotricha (Athias-Henriot) are recorded for the first time from Turkey. Two new species Neoseiulus sekeroglui Döker & Stathakis n. sp. and Typhlodromus (Typhlodromus) antakyaensis Stathakis & Döker n. sp. are described and illustrated. A key to the all known phytoseiid species for the Turkish fauna is also provided.